2022
DOI: 10.3389/fpsyg.2022.911421
|View full text |Cite
|
Sign up to set email alerts
|

Exploring family educational involvement and social skills in Chinese preschoolers: The moderating role of parent-child relationship

Abstract: The purpose of this study was to examine parent-child relationship as a moderator of the association between family educational involvement and the social skills of preschoolers. A total of 4,938 children (M = 5.09-years-old, SD = 0.81) were sampled from 18 preschools in Hebei province, China, and their parents completed a survey packet to collect demographic information, as well as ratings of parental involvement, relationships with their children, and child social skill development. The results of multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
2
1
0
Order By: Relevance
“…The finding is opposite to the study of Laible and Thompson (2002) which indicated that there was an increase conflict in child-parent relationship during the early childhood and preschooler years. However, the result support the preschoolers' sample studies in China (Xu et al, 2018;Li & Liu, 2020;Liu et al, 2022). Similarity, the finding of the present study was consistent with previous work in Malaysia (Ee & Arshat , 2017;Azlina et al, 2019); in Singapore (Chung et al, 2020) and in Indonesia (Riany et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The finding is opposite to the study of Laible and Thompson (2002) which indicated that there was an increase conflict in child-parent relationship during the early childhood and preschooler years. However, the result support the preschoolers' sample studies in China (Xu et al, 2018;Li & Liu, 2020;Liu et al, 2022). Similarity, the finding of the present study was consistent with previous work in Malaysia (Ee & Arshat , 2017;Azlina et al, 2019); in Singapore (Chung et al, 2020) and in Indonesia (Riany et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…However, as a result of the Logistic Regression analysis, it was seen that this relationship disappeared. Similar to our findings, studies reported that they did not find a difference between income status and knowledge and perception about air pollution (24,28). Studies are reporting that they found a difference between family income status and environmental risk perception (18)(19)(20).…”
Section: Discussionsupporting
confidence: 90%
“…For example, children who establish strong relationships with caregivers during early childhood tend to acquire valuable skills to apply to their relationships with peers later on. Liu et al (2022) found that strong parent-child relationships were positively related to the social skills of preschool children. Similarly, Brummelman et al (2019) found that gentle physical contact from parents can reduce children's implicit attention to social threats and increase the confidence of children who experience social anxiety.…”
Section: Introductionmentioning
confidence: 97%